Population and production parameters of sheep under traditional management in semi-arid areas of Africa - Wilson, R.T. (Springer, 1980)
Summarizes results of studies carried out in four traditional sheep societies, the Baqqara in Western Sudan, the Afar of Ethiopia, the Bambara of Mali and the Masai of Kenya, and compares results on the basis of demographic structure by age and sex, animal morphology, growth, breeding female productivity and flock output.